Acute-on-Chronic Anterolateral Tibiofibular Joint Dislocation in a Child. Issue 5 (May 2017) - Gill, Jeewanjit S.; Al-Shibli, Amal; Istasy, Victor; Lim, Rodrick
Abstract : Abstract: Tibiofibular joint injury in children is an uncommon injury. It is usually associated with acute injuries in sports that involve aggressive twisting of the knee, such as soccer and snowboarding. We present a case of a 17-year-old male adolescent who sustained an acute dislocation of the anterolateral tibiofibular joint with routine ambulation, who had a chronic history of subluxation. To our knowledge, this has not been previously reported. The diagnosis requires a high level of awareness and suspicion, and plain radiographs may aid in the diagnosis especially if contralateral comparison views are obtained.